Understanding The Impact of Shadow IT Usage on Perceived Dependency to Identify Key Risk Factors For Organization - Nasution, Angel Anggina; Wibisono, Arif (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The widespread adoption of Shadow IT, which refers to the use of applications and systems without explicit IT department approval, has become a critical concern. This concern is supported by 69% of tech executives, identifying it as a top issue in SaaS adoption, and 65% of remote workers regularly using unauthorized IT solutions. While Shadow IT can enhance productivity, it raises significant risks through perceived dependency, potentially leading to increased operational costs, data breaches, and compliance violations. Despite extensive research on Shadow IT’s security implications, a critical gap exists in understanding its relationship with perceived dependency and subsequent organizational risks. This study explores this relationship using a qualitative case study approach, collecting data through interviews and organizational observations. The data are analyzed using open coding methods and interpreted through the Work System Theory (WST) to examine interactions between work system elements. The findings reveal four forms of perceived dependency: process efficiency, employee cognition, data quality, and absence of dependency. Based on these findings, the key risk factors organizations need to consider are dependency on process efficiency and the cognitive dependency of employees. These insights provide organizations with evidence-based strategies for mitigating the negative impacts of Shadow IT-related dependencies while maintaining operational efficiency.